Detection of Parietaria Mottle Virus by RT-qPCR: An Emerging Virus Native of Mediterranean Area That Undermine Tomato and Pepper Production in Southern Italy - Panno, Stefano; Caruso, Andrea Giovanni; Bertacca, Sofia; Matić, Slavica; Davino, Salvatore; Parrella, Giuseppe (Frontiers in Plant Science, 2021)
Parietaria mottle virus (PMoV) is considered an emerging virus in many countries of the Mediterranean basin, especially on tomato and pepper crops. Symptoms on tomato leaves and fruits can be easily confused with those induced by cucumber mosaic virus with necrogenic satellite RNA (CMV-satRNA), tomato spotted wilt virus (TSWV) or tomato mosaic virus (ToMV). Mixed infection of these viruses has been also reported in some tomato cultivars, with an increase in the complexity of the symptoms and severity of the disease. Although a specific serum and riboprobes have been produced, nowadays no sensitive diagnostic methods are available for the rapid PMoV detection. Here, we have developed a RT-qPCR assay with the aim to establish a more sensitive and specific method for PMoV detection. Specific primers and TaqMan probe were designed and in silico tested with all PMoV isolates available in GenBank. Moreover, this method was evaluated on tomato naturally infected samples from Sicily region (Italy). Results obtained showed that the RT-qPCR assay developed in this work is extremely sensitive, in fact, it is able to detect as few as 10 PMoV RNA copies in tomato total RNA; moreover, it will be a particularly valuable tool for early detection of PMoV. Furthermore, the analyzes on field samples show how this pathogen is increasingly present in tomato crops in the last years, helping to undermine the Italian horticultural sector.